Characterization of different roast types of kapeng barako. - Buligan, Angelo L. (College of Home Economics, University of the Philippines Diliman, 2018)
The roasting process, physicochemical, microbiological, and sensorial characteristics of kapeng barako (, and Café Belardo, in Amadeo, Cavite, were documented. Interview results indicate that both coffee roasters use an almost similar roasting procedure: Kape at Kakao de Batangas starts with a 65kg green coffee beans which were then dehulled then roasted. Once cooled, beans were sorted for two different roasters; Kape at Kakao de Batangas, located in Lipa, Batangas or ground coffee beans. defects and foreign materials. Café Belardo on the other hand starts with 15kg of green coffee beans which were dehulled, sorted then roasted. Roasted coffee beans were then sold as whole beans Coffea liberica) beans from The physicochemical properties of the coffee bean samples, such as bulk density (0.42 g/ml to 0.34 g/ml), L* (28.83 to 19.80), a* (11.98 to 5.30), b* (20.03 to 5.54), moisture content (2.48% to 1.41%), and water activity (0.15 to 0.11), were found to decrease when degree of roast increased while pH (4.91 to 5.62) increased. Caffeine content was not greatly affected by the roasting process with values 1.06 for light roast, 1.10 for medium roast, and 1.05 for dark roast. Aerobic Plate Count (APC) value of < 4.40 log(cfu*g-1) and a Yeast and Mold Count (YMC) value of < 3 log(cfu*g-1) obtained were not enough evidence to assume the products safeness for consumption since the detection limits were higher than the upper limit of the standards. Based on its physicochemical properties (moisture content, Aw, pH), properties, however, microbial proliferation in the final product is unlikely. and flavor that was just right, and a slight remnant of the langka flavor was observed. Lastly, the dark roast embodied the characteristics of the typical kapeng barako. The panelists enjoyed it the most due to its bitterness and strong flavor that they were accustomed to. Results of the Focus Group Discussions done in Barangay Ludlod in Lipa, Batangas indicated that the dark roast had the characteristics similar to the kapeng barako the panelists used to drink. According to the panelists, the light roast produced a nutty and langka (jackfruit) aroma and taste, with a slight bitterness. The medium roast had a bitterness and flavor that was just right, and a slight remnant of the langka flavor was observed. Lastly, the dark roast embodied the characteristics of the typical kapeng barako. The panelists enjoyed it the most due to its bitterness and strong flavor that they were accustomed to.